Neuroendocrine and Peptidergic Regulation of Stress-Induced REM Sleep Rebound - Machado, Ricardo Borges; Suchecki, Deborah (Frontiers in Endocrinology, 2016)
Sleep homeostasis depends on the length and quality (occurrence of stressful events, for instance) of the preceding waking time. Forced wakefulness (sleep deprivation or sleep restriction) is one of the main tools used for the understanding of mechanisms that play a role in homeostatic processes involved in sleep regulation and their interrelations. Interestingly, forced wakefulness for periods longer than 24 h activates stress response systems, whereas stressful events impact on sleep pattern. Hypothalamic peptides (CRH, prolactin and the CLIP/ACTH18-39) play an important role in the expression of stress-induced sleep effects, essentially by modulating REM sleep, which has been claimed to affect the organism resilience to the deleterious effects of stress. Some of the mechanisms involved in the generation and regulation of sleep and the main peptides/hypothalamic hormones involved in these responses will be discussed in this review.